2015
DOI: 10.5296/ije.v7i2.7699
|View full text |Cite
|
Sign up to set email alerts
|

Motivations towards Learning English: The Case of Jordanian Gifted Students

Abstract: <p>The present study aimed at investigating the motivational orientations of Jordanian gifted<br />school students in Ajloun governorate. For this purpose, 51 students from King Abdullah II in<br />Ajloun governorate participated in this study. Data was collected through a questionnaire<br />contained 20 items asking about the motivational level and orientation of learners. The<br />questionnaire was adapted from Gardner’s (1985) AMTB (Attitude, Motivation Test Battery)<br />… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…In the past three decades, more than 800 empirical works have been conducted to explore how an individual's intrinsic and extrinsic motivation affects behavior [20]. Motivation is defined by the present study as an individual learner's drive to learn the subject matter, which has always been acknowledged as a critical factor in learning [21], especially within the context of e-learning [22] and learning a second/foreign language [23], [24]. Nevertheless, motivation has not received enough attention in empirical studies of e-learning [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the past three decades, more than 800 empirical works have been conducted to explore how an individual's intrinsic and extrinsic motivation affects behavior [20]. Motivation is defined by the present study as an individual learner's drive to learn the subject matter, which has always been acknowledged as a critical factor in learning [21], especially within the context of e-learning [22] and learning a second/foreign language [23], [24]. Nevertheless, motivation has not received enough attention in empirical studies of e-learning [25].…”
Section: Introductionmentioning
confidence: 99%
“…That reality raises the curiosity about the reasons for such differences. Though research suggest that single-sex schools are an option for motivating students ( Al-Mahrooqi & Ambu Saidi, 2012;Coskun, 2014), and as many educational systems segregate students based on their genders in higher grades in the Arab world due to cultural and social factors, still female students' motivation for learning English is higher than males (Al-Khasawneh & Al-Omari, 2015;Mathew, Job, Al Damen, & Islam, 2013). This phenomenon in the Arab world should elevates researchers' curiosity to understand the reasons lead to such differences in achievements through more investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study revealed the urgency for English teachers to also develop communicative tests that involve skill integration, in addition to developing the activities that encompass the four language skills. The fifth study by Al-Khasawneh and Al-Omari (2015) from Ajloun National University in Jordan states that the development of learning language is affected by several elements such as attitude, aptitude and motivation. Consequently, learners' activities should be carefully chosen according to how they involve the learner in meaningful and authentic language use.…”
Section: Discussionmentioning
confidence: 99%